IFNγ causes keratinocyte necroptosis in acute graft-versus-host disease - Freund, Lukas; Oehrl, Stephanie; Schwingen, Julius; Häberle, Stefanie; Döbel, Thomas; Lee, Paul D. H.; Meisel, Stefan; Mihalceanu, Silvia; Rußwurm, Martin; Luft, Thomas; Schäkel, Knut (The journal of investigative dermatology, 2023)
Epidermal keratinocytes form the first-line cellular barrier of the skin for protection against external injuries and maintenance of local tissue homeostasis. Expression of ZBP1 was shown to cause necroptotic keratinocyte cell death and skin inflammation in mice. We sought to characterize the relevance of ZBP1 and necroptosis in human keratinocytes and type 1−driven cutaneous acute graft-versus-host disease. in this study, we identify ZBP1 expression, necroptosis, and interface dermatitis as being the hallmarks of acute graft-versus-host disease. ZBP1 expression was dependent on leukocyte-derived IFNγ, and interference with IFNγ signaling by Jak inhibition prevented cell death. In predominantly IL-17−driven psoriasis, both ZBP1 expression and necroptosis could not be detected. Of note, in contrast to the signaling in mice, ZBP1 signaling in human keratinocytes was not affected by RIPK1’s presence. These findings show that ZBP1 drives inflammation in IFNγ-dominant type 1 immune responses in human skin and may further point to a general role of ZBP1-mediated necroptosis.